Case report of chronic cough in primary care: a diagnostic challenge and lessons to learn - Abu Bakar, Anifah; Azmi, Nurul Husna; Md Aris, Mohd Aznan; Khamis@Roslee, Norhayaty Sharman (The Academy of Family Physicians of Malaysia and Family Medicine Specialist Association of Malaysia, 2022)
Cough is one of the most common complaints seen at the outpatient primary health clinic. While the most common aetiologies of chronic cough are asthma, chronic obstructive pulmonary disease, postnasal drip, gastroesophageal reflux disease, drug-induced, and tuberculosis, we often overlook that chronic cough, especially in a young female, can be the initial presenting complaint of an autoimmune disease. In this case report, we present a case of 35-year-old woman with no known prior medical illness who presented with chronic cough for 1 year with no other symptoms initially; but later in the disease course, the patient complained of multiple, symmetrical small joint pain, which led us to the diagnosis of seronegative rheumatoid arthritis.